Temperature-Dependent Demography and Population Projection of Lepidosaphes pistaciae (Archangelskaya; Hemiptera: Diaspididae) Reared on Pistacia vera L. - Ozgen, Inanc; Ozgokce, Mehmet Salih (Springer, 2025)
The pistachio scale insect Lepidosaphes pistaciae (Archangelskaya; Hemiptera: Diaspididae) is a common pest in pistachio plantations, causing major economic losses. It is widespread on pistachio trees in tropical and subtropical regions around the world. In the current study, the biological characteristics and age-stage two-sex life table of L. pistaciae on Pistacia vera L. were examined under laboratory conditions at 25 degrees C and at 30 degrees C (60 +/- 5% RH, 16 h light:8 h dark). The data obtained were analyzed using the age-stage two-sex life table, and the population growth of two cohorts was projected by using the computer simulation. It was found that durations of all preadult stages, total developmental time, mean female longevity, mean longevity of all cohorts, adult pre-oviposition period, and generation times (total pre-oviposition period) of L. pistaciae were significantly shorter at 30 degrees C than at 25 degrees C. The population growth parameters, i.e., the intrinsic rate of increase (r), the finite rate of increase (lambda), net reproduction rate (R0) and mean female fecundity (F) were significantly higher at 30 degrees C (r = 0.063 d-1, lambda = 1.065 d-1, R0 = 60.57 offspring/individual, and F = 69.65 eggs/female) than those at 25 degrees C (r = 0.048 d-1, lambda = 1.050 d-1, R0 = 41.04 offspring/individual, and F = 47.20 eggs/female). Starting with an initial population of 10 eggs, the total number of individuals reached 410 after 100 days at 25 degrees C compared to 601 individuals at 30 degrees C. These results showed that that 30 degrees C is a more favorable temperature for pistachio scale insects than 25 degrees C.
Keywords: Lepidosaphes pistaciae; Pistacia vera; Population projection; Temperature-dependent development; Two-sex life table